First record of Bruchidius apicipennis (Heyden, 1892) (Coleoptera, Chrysomelidae) from Siberia - Legalov, Andrei A. (Ecologica Montenegrina)
The first record of Bruchidius apicipennis (Heyden, 1892) (Chrysomelidae: Bruchinae: Bruchini) from Altaiskii Krai (Western Siberia, Russia) is given. It is the most northern find of this species. The host plant, distribution map, illustrations and redescription of Bruchidius apicipennis are presented.